German Idealism : the Struggle against Subjectivism, 1781-1801. - Beiser, Frederick C. (Harvard University Press, 2008)
One of the very few accounts in English of German idealism, this ambitious work advances and revises our understanding of both the history and the thought of the classical period of German philosophy. As he traces the structure and evolution of idealism as a doctrine, Frederick Beiser exposes a strong objective, or realist, strain running from Kant to Hegel and identifies the crucial role of the early romantics - Hölderlin, Schlegel, and Novalis - as the founders of absolute idealism.